Archaeological and historical insights into the ecological impacts of pre-colonial and colonial introductions into the Philippine Archipelago. (February 2021) - Amano, Noel; Bankoff, Greg; Findley, David Max; Barretto-Tesoro, Grace; Roberts, Patrick
The tropical forests of the Philippine Archipelago are some of the most threatened in the 21st century. Among the most prominent threats are the introduction of new plant and animal species, as well as new forms of land management (e.g. plantations), that have accompanied industrial expansion. Such threats have a potentially long-term history and prehistory in the Philippines, not just as a consequence of Spanish colonial administration and land-use changes from the 16th century, but also in the context of pre-colonial introductions of rice agriculture and domesticated animals. However, the impacts of such arrivals on local Philippine societies and ecologies have remained relatively unexplored, especially in comparison to contemporary exchanges between Europe and the Neotropics. Here, we evaluate archaeological and historical evidence for the integration of novel plants, animals and economic strategies into local Philippine cultures and economies from 4000 years ago to the 19th century AD. This includes material culture, archaeozoological and archaeobotanical analysis, as well as archival references to pre- and post-colonial urban settlements, the evolution of land management and rural settlements across the Archipelago. We argue that prehistoric land-use changes, as well as the colonial introduction of crops and domesticated animals, represent a potentially interesting contrast to other tropical regions that came under Spanish imperial control between the 15th and 19th centuries. Nevertheless, to determine the full extent of their impacts on social organisation and Philippine landscapes more detailed, long-term multidisciplinary investigation is required.